Cypress looper Anacamptodes pergracilis (Hulst) (Insecta: Lepidoptera: Geometridae) - Wayne N. Dixon (EDIS)
Anacamptodes pergracilis (Hulst), commonly known as the cypress looper, drew considerable attention in late summer of 1980 with the unexpected defoliation of nearly 28,000 ha of cypress trees in USFS-NPS Big Cypress National Preserve (Collier and Monroe counties). Currently, cypress looper populations are at low levels, even in the Fisheating Creek (Glades County) area, a perennial generator of significant cypress looper defoliation over the past 20 years. This 3-page fact sheet was written by Wayne N. Dixon and published by the UF Department of Entomology and Nematology, April 2013.